Lysine acetylation of Escherichia coli lactate dehydrogenase regulates enzyme activity and lactate synthesis - Liu, Min; Huo, Meitong; Liu, Changshui; Guo, Likun; Ding, Yamei; Ma, Qingjun; Qi, Qingsheng; Xian, Mo; Zhao, Guang (Frontiers in Bioengineering and Biotechnology, 2022)
As an evolutionarily conserved posttranslational modification, protein lysine acetylation plays important roles in many physiological and metabolic processes. However, there are few reports about the applications of lysine acetylation in metabolic regulations. Lactate is a main byproduct in microbial fermentation, and itself also an important bulk chemical with considerable commercial values in many fields. Lactate dehydrogenase (LdhA) is the key enzyme catalyzing lactate synthesis from pyruvate. Here, we reported that Escherichia coli LdhA can be acetylated and the acetylated lysine sites were identified by mass spectrometry. The effects and regulatory mechanisms of acetylated sites on LdhA activity were characterized. Finally, lysine acetylation was successfully used to regulate the lactate synthesis. LdhA(K9R) mutant overexpressed strain improved the lactate titer and glucose conversion efficiency by 1.74 folds than that of wild-type LdhA overexpressed strain. LdhA(K154Q-K248Q) mutant can inhibit lactate accumulation and improve 3HP production. Our study established a paradigm for lysine acetylation in lactate synthesis regulation and suggested that lysine acetylation may be a promising strategy to improve the target production and conversion efficiency in microbial synthesis. The application of lysine acetylation in regulating lactate synthesis also provides a reference for the treatment of lactate-related diseases.